Design and fabrication of handy loose coconut palm collector - Muhamad Khairul Anuar, Shaharuddin (2013)
The oil palm is a tropical plant that grows in warm climates at altitudes below 500 meters above sea level. It comes from the Gulf of Guinea in West Africa, which explains its scientific name, Elaeis guineensis Jacq. And its popular name, the African oil palm. At the beginning, the oil palm plant grows in the wild and later was developed into an agricultural crop. It was introduced to Malaysia by the British in early 1870’s as an ornamental plant. The first commercial planting took place in Tennamaran Estate in Selangor on 1917, laying the foundations for the vast oil palm plantations and the palm oil industry in Malaysia. Malaysia is one of the largest producers and exporters of palm oil in the world, accounting for 11% of the world’s oil and fats production and 27% of export trade of oils and fats. The palm oil is produced from the fruit of the oil palm tree. It has been used as a food source for thousands of years in Asia and Africa, and it has many non-food uses as well. The palm oil is good on frying and baking. The palm oil is stable and will not break down at high temperatures, so it making ideal for frying and baking. The palm oil is also used to make shortenings, margarines, candies, chocolate, condensed milk, sauces and most important the palm oil is good in cooking oil. Nevertheless, the palm oil is also used to make cosmetics, soaps, candles and detergents. It is also used as lubricant for food manufacturing machinery. Besides, the petroleum, plastics, printing and textile industries all commonly use palm oil. Other than that, palm oil is used to make a sustainable, environmentally friendly fuel for automobiles and machines. The biodiesel fuel becomes more popular in the world. The Colombia country is the one of its major producers.